Modified metal organic framework material as well as preparation method and application thereof

By developing modified metal organic framework materials for catalytic preparation of N-substituted pyrrole compounds, the problems of low selectivity and expensive catalysts in the prior art are solved, and an efficient and sustainable synthesis method is achieved.

CN119570046APending Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311146082.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The selectivity of N-substituted pyrrole compounds in the prior art and the catalysts require expensive metals, resulting in insufficient green and sustainable synthesis.

Method used

A modified metal organic framework material with a wrinkled outer surface and a large water contact angle was developed for catalytic preparation of N-substituted pyrrole compounds. The material forms an open metal center by coordinating water molecules, and regulates the pore surface properties through ligand exchange method, increases the acid amount and mesoporous cavity, and promotes substrate diffusion and product desorption.

Benefits of technology

High reaction efficiency and high product yield of N-substituted pyrrole compounds are achieved, providing a green and sustainable synthesis method that reduces the risk of deactivation of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570046A_ABST
    Figure CN119570046A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of MOFs materials, in particular to a modified metal organic framework material and a preparation method and application thereof. The modified metal organic framework material comprises: a metal center; and at least two organic ligands coordinated to the at least two binding sites of the metal center to form an at least partially crystalline network structure having a plurality of internal pores; wherein the modified metal organic framework material crystal is provided with a wrinkled outer surface, and the contact angle between the modified metal organic framework material and water is 40-120 degrees. The modified metal organic framework material is used for catalytically preparing an N-substituted pyrrole compound (such as a 2, 5-dimethyl-N-substituted pyrrole compound) and has the outstanding characteristics of high reaction efficiency, high product yield and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of MOFs materials, and in particular to a modified metal organic framework material and a preparation method and application thereof. Background Art

[0002] Metal-organic framework materials are periodically arranged network framework crystalline materials that are self-assembled with carboxylic acid or nitrogen-containing organic bridging ligands through coordination bonds using metal ions or metal ion clusters as nodes. Due to the diversity of their structural composition, high specific surface area and porosity, and adjustable pore structure and size, they have broad application prospects in the fields of gas storage and separation, luminescence and detection, catalysis, and drug delivery and controlled release.

[0003] From the study of bulk MOFs materials to nano-size or two-dimensional morphology, from the exploration of the pores of MOFs materials themselves to the construction of multi-level pores, from the preparation of single MOFs materials to the synthesis of MOFs composite materials. In general, it is a process from bulk to miniaturization, nano-scale or further structure; from single to diversified.

[0004] Nitrogen-containing heterocycles, especially functionalized pyrroles, are important structural units of a large number of naturally occurring and pharmacologically active molecules. They are widely used in the core structures of bioactive substances such as vitamins, anticancer drugs, and antibacterial drugs. The main substrates used in traditional N-substituted pyrroles are usually ketones, aldehydes, or amines containing substituents. Most of these raw materials come from petrochemical resources, and the reaction yield is low. It is more important to explore the construction of pyrrole derivatives based on biomass. 2,5-Hexanedione (HDO) has attracted more and more attention as an important biomass platform compound. Researchers synthesize HDO through cellulose or sugar platforms. HDO can react with amines or nitro compounds under the catalysis of appropriate catalysts to undergo Paal-Knorr condensation to generate N-substituted pyrroles. Under suitable catalysts and reaction conditions, high selectivity and yield can be obtained.

[0005] The heterogeneous catalytic dehydrogenative coupling reaction of bio-secondary alcohols with amino alcohols pioneered by the prior art [Nat. Chem. 2013, 5, 140-144; Catal. Sci. Technol. 2014, 4, 4188-4192] has become an important method for constructing pyrrole skeletons. Although the reaction yield is high, the high separation and recovery cost and potential toxicity of iridium species still pose challenges to the establishment of a greener and more sustainable synthesis method. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of low selectivity of N-substituted pyrrole compound products or the need for expensive metals in catalysts in the prior art, and to provide a modified metal organic framework material and a preparation method and application thereof; the modified metal organic framework material of the present invention has a wrinkled outer surface and a contact angle with water of 40-120°; the modified metal organic framework material is used for catalytic preparation of N-substituted pyrrole compounds (such as 2,5-dimethyl-N-substituted pyrrole compounds) and has outstanding characteristics such as high reaction efficiency and high product yield.

[0007] In order to achieve the above object, the first aspect of the present invention provides a modified metal organic framework material, the modified metal organic framework material comprising:

[0008] Metal center; and

[0009] at least two organic ligands coordinated to at least two binding sites of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities;

[0010] The modified metal organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal organic framework material and water is 40-120°.

[0011] The second aspect of the present invention provides a method for preparing the modified metal organic framework material of the present invention, the method comprising the following steps:

[0012] S1, dissolving a soluble metal salt and a first organic ligand in a solvent I, crystallizing, separating, and first drying to obtain a MOFs material formed by the metal and the first organic ligand;

[0013] S2, contacting the MOFs material in step S1 with a solution containing a second organic ligand and an alkaline substance; separating, washing, and performing a second drying to obtain the modified metal organic framework material.

[0014] The third aspect of the present invention provides a use of the modified metal organic framework material of the present invention in the preparation of N-substituted pyrrole compounds.

[0015] Through the above technical scheme, the modified metal organic framework material of the present invention has a wrinkled outer surface, and a contact angle with water of 40-120°. Compared with before modification, it has a certain hydrophobicity. According to a preferred embodiment of the present invention, compared with before modification, the modified metal organic framework material of the present invention has increased acid content and newly formed mesoporous cavities.

[0016] The modified metal organic framework material of the present invention can be easily removed from coordinated water molecules during the preparation process, thereby forming an open metal center as a catalytic center; through the ligand exchange method, the polyazole ligand containing a benzene ring has strong alkalinity, so that the pore surface properties of the metal organic framework material are easier to control, and the nitrogen atom donor participates in the coordination, so that it has a certain hydrophobicity compared to before the modification; the newly formed metal open site increases the acid content of the material, and the newly formed mesoporous cavity effectively promotes the diffusion of the substrate, which is not only beneficial to the substrate adsorption and product desorption, but also increases the yield of the target product and inhibits the deactivation of the catalyst.

[0017] The modified metal organic framework material of the present invention is used for catalytic preparation of N-substituted pyrrole compounds (such as 2,5-dimethyl-N-substituted pyrrole compounds), which can achieve high reaction efficiency and high product yield. The development of this method will provide new ideas for the construction of green synthetic pyrrole compounds, provide a new direction for metal organic framework materials in the field of biomass catalysis, and achieve unexpected technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The scanning electron microscope (SEM) images of Cu-BTC and Cu-BTC-BzIm in Example 1;

[0019] Figure 2 It is the pyridine desorption infrared (Py-FTIR) image of Cu-BTC and Cu-BTC-BzIm in Example 1;

[0020] Figure 3 is the contact angle between Cu-BTC and water in Example 1;

[0021] Figure 4 is the contact angle between Cu-BTC-BzIm and water in Example 1;

[0022] Figure 5 N2- adsorption-desorption curves of Cu-BTC and Cu-BTC-BzIm in Example 1;

[0023] Figure 6 This is the scanning electron microscope (SEM) image of Cu-BTC-BzIm-2 in Example 2. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] In the present invention, the metal center refers to the metal ion used to form a coordination complex in the MOFs material.

[0026] The first aspect of the present invention provides a modified metal organic framework material, the modified metal organic framework material comprising:

[0027] Metal center; and

[0028] at least two organic ligands coordinated to at least two binding sites of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities;

[0029] The modified metal organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal organic framework material and water is 40-120°. The modified metal organic framework material of the present invention has a wrinkled outer surface, and the contact angle between the modified metal organic framework material and water is 40-120°, and it has a certain hydrophobicity compared to before modification.

[0030] According to a preferred embodiment of the present invention, the contact angle between the modified metal organic framework material and water is 40-100°.

[0031] According to a preferred embodiment of the present invention, clusters of flake-like protrusions are distributed on the surface of the modified metal organic framework material crystal to form a wrinkled outer surface.

[0032] According to a preferred embodiment of the present invention, the total acid content of the modified metal organic framework material is 30-500 μmol·g -1 , preferably 40-400 μmol·g -1 .

[0033] According to a preferred embodiment of the present invention, the total specific surface area of ​​the modified metal organic framework material is 900-1800m 2 ·g -1 , external specific surface area is 40-200m 2 ·g -1 .

[0034] According to a preferred embodiment of the present invention, the total pore volume of the modified metal organic framework material is 0.4-1.0 cm 3 ·g -1 , the micropore volume is 0.2-0.9cm 3 ·g -1 .

[0035] In the present invention, the total pore volume of the modified metal organic framework material is the sum of the micropore volume and the mesopore volume.

[0036] In the present invention, the metal of the metal center can be selected from a wide range. According to a preferred embodiment of the present invention, the metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al, and is preferably at least one of Zn, Cu, Ni, Fe, Co and Zr.

[0037] According to a preferred embodiment of the present invention, the organic ligand includes a first organic ligand and a second organic ligand, the first organic ligand is selected from at least one of carboxylic acid organic ligands; the second organic ligand is selected from at least one of polyazole organic ligands containing a benzene ring.

[0038] According to a preferred embodiment of the present invention, the first organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid and 3,3,5,5-biphenyl tetracarboxylic acid.

[0039] According to a preferred embodiment of the present invention, the second organic ligand is at least one selected from benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxybenzene)benzimidazole, 2-aminobenzimidazole and 2-(4'-thiazole)benzimidazole.

[0040] The modified metal organic framework materials having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the modified metal organic framework material of the present invention, which comprises the following steps:

[0041] S1, dissolving a soluble metal salt and an organic ligand I in a solvent I, crystallizing, separating, and first drying to obtain a MOFs material formed by the metal and the organic ligand I;

[0042] S2, contacting the MOFs material in step S1 with a solution containing organic ligand II and alkaline substances; separating, washing, and performing a second drying to obtain the modified metal organic framework material.

[0043] The modified metal organic framework material of the present invention can be easily removed from coordinated water molecules during the preparation process, thereby forming an open metal center as a catalytic center; through the ligand exchange method, the polyazole ligand containing a benzene ring has strong alkalinity, so that the pore surface properties of the metal organic framework material are easier to control, and the nitrogen atom donor participates in the coordination, so that it has a certain hydrophobicity compared to before the modification; the newly formed metal open site increases the acid content of the material, and the newly formed mesoporous cavity effectively promotes the diffusion of the substrate, which is not only beneficial to the substrate adsorption and product desorption, but also increases the yield of the target product and inhibits the deactivation of the catalyst.

[0044] In the present invention, there is no particular limitation on the type of the soluble metal salt, and it may be, for example, a soluble salt such as a metal nitrate, a metal chloride, or a metal sulfate.

[0045] In the present invention, in step S1, the optional range of the dosage ratio of the soluble metal salt to the organic ligand I is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of the soluble metal salt to the organic ligand I is 1:0.2-5.

[0046] In the present invention, in step S1, the optional range of the usage ratio of solvent I to soluble metal salt is relatively wide. According to a preferred embodiment of the present invention, the usage ratio of solvent I to soluble metal salt is 5-100 mL solvent I / 1.0 g soluble metal salt.

[0047] In the present invention, in step S2, the optional range of the usage ratio of MOFs material to organic ligand II is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of MOFs material to organic ligand II is 1:(0.01-5).

[0048] In the present invention, in step S2, the optional range of the usage ratio of MOFs material to alkaline substance is relatively wide. According to a preferred embodiment of the present invention, the molar ratio of MOFs material to alkaline substance is 1:(0.01-3).

[0049] In the present invention, in step S2, in the solution containing organic ligand II and alkaline substance, the range of solvents available for selection is relatively wide. According to a preferred embodiment of the present invention, the solvent is solvent II, and solvent II is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene and ethylbenzene. Preferably, the mass ratio of MOFs material to solvent II is 1:(2-200).

[0050] In the present invention, in step S2, the type of the alkaline substance can be selected from a wide range, as long as it is an organic base or an inorganic base with weak alkalinity. According to a preferred embodiment of the present invention, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, ammonia water and aniline.

[0051] According to a preferred embodiment of the present invention, the organic ligand I is the first organic ligand.

[0052] According to a preferred embodiment of the present invention, the organic ligand II is a second organic ligand.

[0053] According to a preferred embodiment of the present invention, the method for preparing the modified metal organic framework material further includes, in step S2, soaking the washed solid in a solvent III, wherein the solvent III is selected from at least one of methanol, ethanol, dichloromethane and acetone; the preferred soaking conditions include: the soaking temperature is 0-50°C; the mass ratio of the solid to the solvent III is 1:10-300.

[0054] In the present invention, the soaking time can be determined according to actual needs. According to a preferred embodiment of the present invention, the soaking time is 10-96 hours, and the solvent III is replaced every 2-24 hours.

[0055] In the present invention, in step S1, the range of crystallization conditions is relatively wide. According to a preferred embodiment of the present invention, the crystallization conditions include: a crystallization temperature of 30-200°C, preferably 50-160°C; the reaction time can be reasonably determined according to actual needs, preferably, the crystallization time is 3-44h, preferably 5-24h.

[0056] In the present invention, in step S1, the first drying condition has a wide range of optional options. According to a preferred embodiment of the present invention, the first drying condition includes: a drying temperature of 70-200°C; the drying time can be reasonably determined according to actual needs, and the drying time is 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.

[0057] In the present invention, in step S2, the contact conditions have a wide range of optional contact conditions. According to a preferred embodiment of the present invention, the contact conditions include: a contact temperature of 30-180°C, preferably 50-110°C; the contact time can be reasonably determined according to actual needs, preferably 3-30h, preferably 6-20h.

[0058] In the present invention, in step S2, the second drying condition has a wide range of optional options. According to a preferred embodiment of the present invention, the second drying condition includes: a drying temperature of 70-200°C; the drying time can be reasonably determined according to actual needs, and the preferred drying time is 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: a temperature of 70-100°C and a time of 1-24h; the second step drying conditions include: a temperature of 120-200°C and a time of 1-24h.

[0059] The third aspect of the present invention provides an application of the modified metal organic framework material of the present invention in the preparation of N-substituted pyrrole compounds. The modified metal organic framework material of the present invention is used for catalytic preparation of N-substituted pyrrole compounds (such as 2,5-dimethyl-N-substituted pyrrole compounds), which can achieve high reaction efficiency and high product yield.

[0060] The present invention provides a method for preparing a 2,5-dimethyl-N-substituted pyrrole compound, the method comprising:

[0061] In the presence of a liquid diluent and a catalyst, 2,5-hexanedione is contacted with an amine compound; the catalyst contains the modified metal organic framework material of the present invention.

[0062] In the present invention, the types of the amine compounds can be selected from a wide range. According to a preferred embodiment of the present invention, the amine compounds are selected from at least one of aniline, m-chloroaniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-hydroxyaniline, n-hexylamine, furfuralamine, naphthylamine, 2-thiophenemethylamine and benamine.

[0063] In the present invention, there is no particular limitation on the type of the liquid diluent, as long as it does not react with the substrate, conventional liquid diluents in the art can be used in the present invention. According to a preferred embodiment of the present invention, the liquid diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, n-hexane, dichloromethane, tetrahydrofuran, acetone and methyl isobutyl ketone.

[0064] In the present invention, the range of the optional amount ratio of 2,5-hexanedione to the catalyst is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of 2,5-hexanedione to the catalyst is 1-100:1, preferably 2-30:1.

[0065] In the present invention, the range of the optional amount ratio of 2,5-hexanedione to the amine compound is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of 2,5-hexanedione to the amine compound is 0.2-100:1, preferably 0.5-50:1.

[0066] In the present invention, the range of the ratio of the liquid diluent to 2,5-hexanedione is relatively wide. According to a preferred embodiment of the present invention, the mass ratio of the liquid diluent to 2,5-hexanedione is 0-200:1, preferably 5-50:1.

[0067] In the present invention, the contact conditions of 2,5-hexanedione and amine compounds can be selected in a wide range. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 100-220°C, preferably 120-200°C; and / or a time of 1-24h, preferably 4-20h.

[0068] In the present invention, the reaction product N-substituted pyrrole compound is analyzed qualitatively and quantitatively by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of the product soluble carbohydrate is analyzed by high performance liquid chromatography (HPLC). The gas chromatography-mass spectrometer is Agilent 7890A of Agilent Corporation of the United States, the chromatographic column is HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph is Agilent 7890B, the detector is hydrogen flame ionization detector (FID), and the chromatographic column is SE-54 capillary column (30m, 0.53mm). The high performance liquid chromatography adopts Agilent 1200 analysis, and the chromatographic column is SHODEX SC1011 sugar column (8×300mm).

[0069] The acid content and acid type of metal organic framework materials were determined by pyridine adsorption infrared method (Nicolet Model 710 spectrometer). The specific operation steps are as follows: a. Sample pretreatment. The sample (about 30 mg) was pressed into a thin disc with a diameter of 13 mm and loaded into the infrared sample tank. After that, the sample was pretreated for 1 hour under vacuum cell conditions and 150°C. After the sample tank was cooled to room temperature, the sample infrared data was scanned as the background. b. Pyridine adsorption. At room temperature and vacuum environment, pyridine vapor was introduced into the original position until the adsorption reached equilibrium, and the adsorption time was 1 hour. c. Pyridine desorption. After the adsorption was completed, vacuum was evacuated at 100°C until the internal pressure no longer changed. The desorption time was 40 minutes, and the infrared absorption spectrum was scanned and recorded respectively. The difference spectrum before and after pyridine adsorption is the obtained pyridine adsorption-infrared absorption spectrum. The acid content of the sample was semi-quantitatively calculated based on the spectrum:

[0070]

[0071]

[0072] Where r and w are the diameter (cm) and mass (g) of the catalyst disc, A is the absorbance integral value at the specified wave number peak based on the scanning pyridine adsorption-infrared absorption spectrum, IMEC is the integrated molar extinction coefficient, IMECL is 2.22, and IMECB is 1.67.

[0073] The XRD measurement method is: the phase of the sample is analyzed using a Rigaku Ultima IV X-ray powder diffractometer from Japan, with a CuKα ray source. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.

[0074] In the present invention, the contact angle measuring instrument is DSA100 of KRUSS Company, Germany. A tangent line of the gas-liquid interface is drawn from the intersection of the gas, liquid and solid phases, and the angle θ between the tangent line and the solid-liquid boundary line passing through the three-phase contact point is the contact angle of the liquid on the solid surface. When the gas is air, the solid is the modified MOF material, and the liquid is water, the measured contact angle is the contact angle between the modified MOFs material and water, wherein the larger the contact angle, the better the relative hydrophobicity of the modified MOFs catalyst.

[0075] In the present invention, the scanning electron microscope (SEM) photos of the samples were taken on a Hitachi S-4800II scanning electron microscope. The acceleration voltage of the instrument was 15 kV, and the samples were chrome-plated before analysis.

[0076] In the present invention, the test instrument and test method for the average pore size, specific surface area and pore volume of the sample are: physical adsorption measurement is performed by nitrogen at -196°C using a 3H-2000PM2 physical adsorption instrument to analyze the pore structure characteristics of each adsorption material sample. The initial degassing condition is: degassing operation at 150°C for 6 hours. After measuring the adsorption isotherm of nitrogen on the sample, the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) method, and the pore volume and pore size distribution are calculated using the BJH (Barrett-Joyner-Halenda) method.

[0077] Conversion rate of 2,5-hexanedione % = (molar amount of 2,5-hexanedione participating in the reaction) / (molar amount of 2,5-hexanedione as a reaction substrate)×100%.

[0078] The yield of the product 2,5-dimethyl-N-substituted pyrrole compound (%) = (the molar amount of 2,5-dimethyl-N-substituted pyrrole produced by the reaction) / (the molar amount of the reaction substrate 2,5-hexanedione) × 100%.

[0079] The selectivity of the product 2,5-dimethyl-N-substituted pyrrole (%) = (the molar amount of 2,5-dimethyl-N-substituted pyrrole produced by the reaction) / (the molar amount of 2,5-hexanedione reacted)×100%.

[0080] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments, but the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0081] Example 1

[0082] S1. Weigh 3g of trimesic acid and add it to a mixture of 70mL of anhydrous ethanol and 40mL of DMF, and stir it thoroughly for 20min. Weigh 6g of copper nitrate trihydrate and dissolve it in 70mL of H2O, then mix the two solutions, stir the mixture thoroughly and put it into a reactor, and crystallize it at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with ethanol several times. Drying is carried out in two stages, the temperature of the first stage is 75℃, the time is 4h, and the drying temperature of the second stage is 150℃, and the time is 10h. Then, vacuum dry it at 100℃ for 10h to obtain Cu-BTC.

[0083] S2, weigh 0.6g benzimidazole (BzIm) and add it to 80mL methanol, stir it thoroughly to obtain a methanol solution; weigh 1.2g Cu-BTC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir it thoroughly for 6h. The solution was placed in a reactor and crystallized at 80°C for 16h. After crystallization, it was cooled to room temperature, centrifuged to remove the mother liquor, and washed with methanol. Drying was carried out in two stages, the temperature of the first stage was 75°C and the time was 4h. After drying, it was soaked in dichloromethane for 48h, and it was replaced every 24h. The drying temperature of the second stage was 150°C and the time was 10h. After that, it was vacuum dried at 100°C for 10h to obtain hydrophobic Cu-BTC-BzIm.

[0084] The SEM images of samples Cu-BTC and Cu-BTC-BzIm are shown in Figure 1 As shown, the SEM image of Cu-BTC is Figure 1 As shown in (a), the crystal is a regular octahedron with a smooth surface and a crystal size of 12-18 μm. Figure 1 As shown in (b), the crystal form of Cu-BTC-BzIm has not changed significantly, but there are clustered flake-like protrusions on the surface, forming a wrinkled outer surface.

[0085] Pyridine desorption infrared spectroscopy of samples Cu-BTC and Cu-BTC-BzIm Figure 2 As shown by Figure 2 The total acid content of Cu-BTC-BzIm was calculated to be 178.6 μmol·g -1 The total acid content of Cu-BTC is 50.3 μmol·g -1 .

[0086] Cu-BTC has hydrophilicity because the ligands in the material are carboxylic acids. Figure 3 After modification with imidazole ligands containing benzene rings, Cu-BTC-BzIm material has a certain degree of hydrophobicity compared to Cu-BTC, and the contact angle test diagram is shown in Figure 4As shown, the contact angle of Cu-BTC-BzIm with water is 78-81°.

[0087] The nitrogen adsorption and desorption curves of Cu-BTC and Cu-BTC-BzIm are as follows Figure 5 As shown; Among them, the specific surface area of ​​Cu-BTC is 1572.8m 2 ·g -1 , external specific surface area 43.1m 2 ·g -1 , total pore volume 0.72cm 3 ·g -1 、0.62cm 3 ·g -1 ;

[0088] Cu-BTC-BzIm specific surface area 1316.1m 2 ·g -1 , external specific surface area 78.8m 2 ·g -1 , total pore volume 0.77cm 3 ·g -1 、0.38cm 3 ·g -1 Compared with Cu-BTC, the total specific surface area of ​​Cu-BTC-BzIm material is reduced, but the external specific surface area is increased, the micropore volume is reduced, and therefore the mesopore / macroporous volume is increased.

[0089] Example 2

[0090] S1. Weigh 3g of trimesic acid and add it to a mixture of 70mL of anhydrous ethanol and 40mL of DMF, and stir it thoroughly for 20min. Weigh 6g of copper nitrate trihydrate and dissolve it in 70mL of H2O, then mix the two solutions, stir the mixture thoroughly and put it into a reactor, and crystallize it at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with ethanol several times. Drying is carried out in two stages, the temperature of the first stage is 75℃, the time is 4h, and the drying temperature of the second stage is 150℃, and the time is 10h. Then, vacuum dry it at 100℃ for 10h to obtain Cu-BTC.

[0091] S2, weigh 1.2g benzimidazole and add it to 80mL methanol, stir well to obtain a methanol solution. Weigh the Cu-BTC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir well for 6h. Then put the above solution into a reactor and crystallize it at 80°C for 16h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with methanol. Drying is carried out in two stages, the temperature of the first stage is 75°C and the time is 4h. After drying, soak it in dichloromethane for 48h, changing it every 24h. The drying temperature of the second stage is 150°C and the time is 10h. After that, vacuum dry it at 100°C for 10h to obtain hydrophobic Cu-BTC-BzIm-2.

[0092] The SEM image of Cu-BTC-BzIm-2 is as follows Figure 6 As shown, there are clusters of plate-like protrusions on the crystal surface, forming a wrinkled outer surface, and in contrast Figure 1 (b) The clustered lamellar protrusions are denser.

[0093] The total acid content of Cu-BTC-BzIm-2 is 159.3 μmol·g -1 , hydrophobic angle is 90°, specific surface area is 1200.7m 2 ·g -1 , external specific surface area 61.5m 2 ·g -1 , total pore volume 0.68cm 3 ·g -1 、0.35cm 3 ·g -1 .

[0094] Example 3

[0095] The method of Example 1 is followed, except that in step S2, 0.4 g of benzimidazole replaces 0.6 g of benzimidazole, and the remaining conditions are the same as those of Example 1, to obtain Cu-BTC-BzIm-3.

[0096] The SEM image of Cu-BTC-BzIm-3 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0097] The total acid content of Cu-BTC-BzIm-3 is 175.5 μmol·g -1 , the hydrophobic angle is about 72°, and the specific surface area is 1408.9m 2 ·g -1 , External specific surface area 55.2m 2 ·g -1 , total pore volume 0.7cm 3 ·g -1 、0.49cm3 ·g -1 .

[0098] Example 4

[0099] The method of Example 1 is followed, except that in step S2, the amount of triethylamine used is 2.4 g; the other conditions are the same as those of Example 1, to obtain Cu-BTC-BzIm-4.

[0100] The SEM image of Cu-BTC-BzIm-4 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0101] The total acid content of Cu-BTC-BzIm-4 is 147.1 μmol·g -1 , the hydrophobic angle is about 65°, and the specific surface area is 1219.5m 2 ·g -1 , External specific surface area 50.7m 2 ·g -1 , total pore volume 0.61cm 3 ·g -1 、0.37cm 3 ·g -1 .

[0102] Example 5

[0103] The method of Example 1 is followed, except that in step S2, 80 mL of toluene is used instead of 80 mL of methanol, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-5.

[0104] The SEM image of Cu-BTC-BzIm-5 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0105] The total acid content of Cu-BTC-BzIm-5 is 166.2 μmol·g -1 , the hydrophobic angle is about 95°, and the specific surface area is 1299.3m 2 ·g -1 , external specific surface area 89.2m 2 ·g -1 , total pore volume 0.75cm 3 ·g -1 、0.32cm 3 ·g -1 .

[0106] Example 6

[0107] The method of Example 1 is followed, except that in step S2, 80 mL of ethanol is used instead of 80 mL of methanol, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-6.

[0108] The SEM image of Cu-BTC-BzIm-6 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0109] The total acid content of Cu-BTC-BzIm-6 is 177.9 μmol·g -1 , the hydrophobic angle is about 82°, and the specific surface area is 1357.8m 2 ·g -1 , external specific surface area 80.7m 2 ·g -1 , total pore volume 0.78cm 3 ·g -1 、0.41cm 3 ·g -1 .

[0110] Example 7

[0111] The method of Example 1 is followed, except that in step S2, 0.6 g of 2-methylbenzimidazole is used instead of benzimidazole, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-7.

[0112] The SEM image of Cu-BTC-BzIm-7 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0113] The total acid content of Cu-BTC-BzIm-7 is 170.4 μmol·g -1 , the hydrophobic angle is about 86°, and the specific surface area is 1309.2m 2 ·g -1 , external specific surface area 81.6m 2 ·g -1 , total pore volume 0.76cm 3 ·g -1 、0.39cm 3 ·g -1 .

[0114] Example 8

[0115] The method of Example 1 is followed, except that in step S2, 0.6 g of 5,6-dimethylbenzimidazole is used instead of benzimidazole, and the other conditions are the same as those of Example 1 to obtain Cu-BTC-BzIm-8.

[0116] The SEM image of Cu-BTC-BzIm-8 is similar to the morphology image of Cu-BTC-BzIm in Example 1.

[0117] The total acid content of Cu-BTC-BzIm-8 is 165.1 μmol·g -1 , the hydrophobic angle is about 91°, and the specific surface area is 1281.1m2 ·g -1 , external specific surface area 82.3m 2 ·g -1 , total pore volume 0.69cm 3 ·g -1 、0.34cm 3 ·g -1 .

[0118] Example 9

[0119] The method of Example 1 is followed, except that in step S1, 2.4 g of terephthalic acid is used instead of 3 g of trimesic acid, and the other conditions are the same as those of Example 1, to obtain Cu-BDC-BzIm.

[0120] The crystals are multifaceted cubic.

[0121] The total acid content of Cu-BDC-BzIm is 125.8 μmol·g -1 , the hydrophobic angle is about 70°, and the specific surface area is 1003.5m 2 ·g -1 , External specific surface area 35.4m 2 ·g -1 , total pore volume 0.59cm 3 ·g -1 、0.3cm 3 ·g -1 .

[0122] Example 10

[0123] S1. Weigh 2.4g of terephthalic acid and add it to a mixture of 70mL of anhydrous ethanol and 40mL of DMF, and stir it thoroughly for 20min. Weigh 7.38g of zinc nitrate hexahydrate and dissolve it in 70mL of H2O, then mix the two solutions, stir the mixture thoroughly and put it into a reactor, and crystallize it at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with ethanol several times. Drying is carried out in two stages, the temperature of the first stage is 75℃, the time is 4h, and the drying temperature of the second stage is 150℃, and the time is 10h. Then, vacuum dry it at 100℃ for 10h to obtain Zn-BDC.

[0124] S2, weigh 0.6g benzimidazole (BzIm) and add it to 80mL methanol, stir it thoroughly to obtain a methanol solution; weigh 1.2g Zn-BDC prepared in step S1 and add it to the methanol solution, control the speed at 400-600r / min, then add 0.8g triethylamine dropwise and stir it thoroughly for 6h. Put the solution into a reactor and crystallize it at 80℃ for 16h. After crystallization, cool it to room temperature, centrifuge to remove the mother liquor, and wash it with methanol. Drying is carried out in two stages, the temperature of the first stage is 75℃, and the time is 4h. After drying, soak it in dichloromethane for 48h, changing it every 24h. The drying temperature of the second stage is 150℃, and the time is 10h. Then, vacuum dry it at 100℃ for 10h to obtain hydrophobic Zn-BDC-BzIm.

[0125] The crystals are multifaceted cubic.

[0126] The total acid content of Zn-BDC-BzIm is 143.2 μmol·g -1 The hydrophobic angle is about 79° and the specific surface area is 1689.4m 2 ·g -1 , external specific surface area 85.3m 2 ·g -1 , total pore volume 0.89cm 3 ·g -1 、0.52cm 3 ·g -1 .

[0127] Examples 11-20

[0128] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g of the catalyst in Example 1-10, 2.0g of 2,5-hexanedione, 1.2g of aniline and 10g of methanol were added to a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 150°C for 6h, and the reaction solution was analyzed to obtain the conversion rate of 2,5-hexanedione and the yield of the target product 2,5-dimethyl-1-phenylpyrrole, as shown in Table 1.

[0129] Table 1 Catalytic evaluation results of Examples 11-20

[0130]

[0131] Embodiment 21

[0132] The method of Example 11 is followed, except that the amount of catalyst used is 0.1 g, and the other conditions are the same as Example 11.

[0133] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 97.1% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.8%.

[0134] Embodiment 22

[0135] The method of Example 11 is followed, except that the amount of catalyst used is 0.5 g, and the other conditions are the same as Example 11.

[0136] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 98.9%; and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.5%.

[0137] Embodiment 23

[0138] The method of Example 11 was followed, except that the reaction was carried out at 180°C for 6 hours, and the other conditions were the same as those of Example 11.

[0139] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 99.7% and the yield of the target product 2,5-dimethyl-1-benzylpyrrole was 97.2%.

[0140] Embodiment 24

[0141] The method of Example 11 was followed, except that the reaction was carried out at 120°C for 6 hours, and the other conditions were the same as those of Example 11.

[0142] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 96.8% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.7%.

[0143] Embodiment 25

[0144] The method of Example 11 was followed, except that the reaction was carried out at 150°C for 12 hours, and the other conditions were the same as those of Example 11.

[0145] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 99.8% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.1%.

[0146] Embodiment 26

[0147] The method of Example 11 was followed, except that the amount of aniline used was 0.6 g, and the other conditions were the same as Example 11.

[0148] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 93.2% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 92.8%.

[0149] Embodiment 27

[0150] The method of Example 11 is followed, except that tetrahydrofuran is used instead of methanol, and the other conditions are the same as Example 11.

[0151] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 97.6%; and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.9%.

[0152] Embodiment 28

[0153] The method of Example 11 is followed, except that toluene is used instead of methanol, and the other conditions are the same as Example 11.

[0154] The reaction solution was analyzed to find that the conversion rate of 2,5-hexanedione was 98.2% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 97.8%.

[0155] Embodiment 29

[0156] The method of Example 11 is followed, except that the amine compound is m-toluidine, and the other conditions are the same as Example 11.

[0157] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 98.1%; the yield of the target product 2,5-dimethyl-1-m-benzyl-1-H-pyrrole was 80.3%.

[0158] Embodiment 30

[0159] The method of Example 11 is followed, except that the amine compound is p-methoxyaniline, and the other conditions are the same as Example 11.

[0160] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 97.2%; the yield of the target product 1-(4-methoxyphenyl)-2,5-dimethyl-1H-pyrrole was 78.5%.

[0161] Embodiment 31

[0162] The method of Example 11 is followed, except that the amine compound is m-chloroaniline, and the other conditions are the same as Example 11.

[0163] Analysis of the reaction solution revealed that the conversion rate of 2,5-hexanedione was 99.2%; the yield of the target product 1-(3-chlorophenyl)-2,5-dimethyl-1H-pyrrole was 93.4%.

[0164] Comparative Example 1

[0165] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g HY(37), 2.0g 2,5-hexanedione and 1.2g aniline were added into a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 150℃ for 6h. The reaction liquid was analyzed to obtain a 2,5-hexanedione conversion rate of 88.5% and a target product 2,5-dimethyl-1-phenylpyrrole yield of 72.7%.

[0166] Comparative Example 2

[0167] With 2,5-hexanedione and aniline as substrates and methanol as reaction solvent, 0.2g H-Beta (100), 2.0g 2,5-hexanedione and 1.2g aniline were added to a stirred autoclave. 1MPa nitrogen was introduced to prevent the organic solvent from boiling. The heating jacket was heated to the preset temperature using a programmed temperature increase, and then stirred using a magnetic stirrer. The reaction was carried out at 150°C for 6h, and the reaction liquid was analyzed to obtain a 2,5-hexanedione conversion rate of 72.5%, and a target product 2,5-dimethyl-1-phenylpyrrole yield of 66.9%.

[0168] Comparative Example 3

[0169] The method of Example 11 was followed, except that Cu-BTC prepared according to the method of Example 1 was used instead of Cu-BTC-BzIm. The other conditions were the same as those of Example 11. Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 82.7%, and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 73.8%.

[0170] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified metal organic framework material, characterized in that: The modified metal organic framework material comprises: Metal center; and at least two organic ligands coordinated to at least two binding sites of the metal center to form an at least partially crystalline network structure having a plurality of internal porosities; The modified metal organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal organic framework material and water is 40-120°.

2. The modified metal organic framework material according to claim 1, wherein The contact angle between the modified metal organic framework material and water is 40-100°; and / or Clusters of flake-like protrusions are distributed on the surface of the modified metal organic framework material crystal to form a wrinkled outer surface.

3. The modified metal organic framework material according to claim 1 or 2, wherein: The total acid content of the modified metal organic framework material is 30-500 μmol·g -1 , preferably 40-400 μmol·g -1 ; and / or The total specific surface area of ​​the modified metal organic framework material is 900-1800m 2 ·g -1 , external specific surface area is 40-200m 2 ·g -1 ; and / or The total pore volume of the modified metal organic framework material is 0.4-1.0 cm 3 ·g -1 , the micropore volume is 0.2-0.9cm 3 ·g -1 .

4. The modified metal organic framework material according to any one of claims 1 to 3, wherein: The metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al, preferably at least one of Zn, Cu, Ni, Fe, Co and Zr; The organic ligand comprises a first organic ligand and a second organic ligand, wherein the first organic ligand is selected from at least one of carboxylic acid organic ligands; and the second organic ligand is selected from at least one of polyazole organic ligands containing a benzene ring.

5. The modified metal organic framework material according to any one of claims 1 to 4, wherein: The first organic ligand is selected from at least one of trimesic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid and 3,3,5,5-biphenyl tetracarboxylic acid; and / or The second organic ligand is at least one selected from benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxyphenyl)benzimidazole, 2-aminobenzimidazole and 2-(4′-thiazole)benzimidazole.

6. The method for preparing the modified metal organic framework material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1, dissolving a soluble metal salt and an organic ligand I in a solvent I, crystallizing, separating, and first drying to obtain a MOFs material formed by the metal and the organic ligand I; S2, contacting the MOFs material in step S1 with a solution containing organic ligand II and alkaline substances; separating, washing, and performing a second drying to obtain the modified metal organic framework material.

7. The preparation method according to claim 6, wherein: In step S1, the molar ratio of the soluble metal salt to the organic ligand I is 1:0.2-5; and / or In step S1, the ratio of the solvent I to the soluble metal salt is 5-100 mL of solvent I / 1.0 g of soluble metal salt; and / or In step S2, the molar ratio of MOFs material to organic ligand II is 1:(0.01-5); and / or In step S2, the molar ratio of MOFs material to alkaline substance is 1:(0.01-3); and / or In step S2, in the solution containing organic ligand II and alkaline substance, the solvent is solvent II, and solvent II is selected from at least one of N, N-dimethylformamide, N, N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene and ethylbenzene, and preferably the mass ratio of MOFs material to solvent II is 1: (2-200); and / or In step S2, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, aqueous ammonia and aniline; Preferably, The organic ligand I is a first organic ligand; and / or Organic ligand II is the second organic ligand.

8. The preparation method according to claim 6 or 7, wherein: Step S2 further includes soaking the washed solid in a solvent III, wherein the solvent III is selected from at least one of methanol, ethanol, dichloromethane and acetone; Preferred soaking conditions include: soaking temperature of 0-50°C; and / or The mass ratio of the solid to the solvent III is 1:10-300; and / or The soaking time is 10-96 hours, and the solvent III is replaced every 2-24 hours.

9. The preparation method according to any one of claims 6 to 8, wherein: In step S1, the crystallization conditions include: a crystallization temperature of 30-200° C., preferably 50-160° C.; and / or a crystallization time of 3-44 h, preferably 5-24 h; and / or In step S1, the first drying condition includes: a drying temperature of 70-200°C; and / or a drying time of 2-48h; preferably, the drying is carried out in steps, and the first drying condition includes: a temperature of 70-100°C and a time of 1-24h; the second drying condition includes: a temperature of 120-200°C and a time of 1-24h; and / or In step S2, the contact conditions include: a contact temperature of 30-180°C, preferably 50-110°C; and / or a contact time of 3-30h, preferably 6-20h. In step S2, the second drying conditions include: drying temperature of 70-200°C; and / or drying time of 2-48h; preferably, drying is performed in steps, and the first step drying conditions include: temperature of 70-100°C, time of 1-24h; the second step drying conditions include: temperature of 120-200°C, time of 1-24h.

10. Use of the modified metal organic framework material according to any one of claims 1 to 5 in the preparation of N-substituted pyrrole compounds.

Citation Information

Patent Citations

  • Composite metal organic framework material and preparation method thereof

    CN113121834A

  • Method for directionally regulating and controlling pore structure and hydrophilicity of metal organic framework material, material and application

    CN113372565A

  • Double-ligand metal organic framework material as well as preparation method and application thereof

    CN114479096A

  • Polymer-metal organic framework materials and methods of using the same

    US20160361702A1